Flexible word position coding in reading: Roles for attention and memory. - Snell, Joshua (Memory & Cognition, 2025)
Readers may fail to notice the error in 'Do love you me?': this is the recently established transposed-word (TW) phenomenon. Word position coding is a novel cognitive construct, and researchers are presently debating the underlying mechanisms. Here I investigated roles for attention and memory. Participants (N = 54) made grammaticality judgements to four-word sequences that formed correct sentences ('The man can run', 'The dog was here'), TW sentences ('The can man run', 'The was dog here'), or ungrammatical control sentences ('The man dog run', 'The was can here'). Sequences were replaced by post-masks after 200 ms, and that post-mask was accompanied by a 50-ms retro-cue in the form of an 'X' presented at a critical location (where one could have locally inferred grammaticality; e.g., between the first and second word of 'The was dog here') or a non-critical location (e.g., between the third and fourth word of 'The was dog here'). TW sentences were harder to reject than control sentences – the classic TW effect – and crucially, this effect was modulated by cue validity, with valid cues attenuating TW effects compared to invalid cues. The present results suggest that focused attention aids the process of binding words to locations. Furthermore, as cues appeared after sentence offset, these results suggest that word position coding may take place in memory.